2021
DOI: 10.1186/s12943-021-01372-0
|View full text |Cite
|
Sign up to set email alerts
|

Circ3823 contributes to growth, metastasis and angiogenesis of colorectal cancer: involvement of miR-30c-5p/TCF7 axis

Abstract: Background Colorectal cancer (CRC) is one of the most common malignant tumours. The recurrence and metastasis of CRC seriously affect the survival rate of patients. Angiogenesis is an extremely important cause of tumour growth and metastasis. Circular RNAs (circRNAs) have been emerged as vital regulators for tumour progression. However, the regulatory role, clinical significance and underlying mechanisms still remain largely unknown. Methods High-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(92 citation statements)
references
References 54 publications
1
90
1
Order By: Relevance
“…Increasing studies revealed the important functions of ceRNA network in tumor proliferation, antiapoptosis, metastasis and other tumor development processes. For example, circ3823 contributes to growth, metastasis and angiogenesis of colorectal cancer by absorbing miR-30c-5p and mediating TCF7 [ 48 ]. In addition to this, the resistant tumors showed significant expression changes of circRNAs, CircMEMO1 modulates the promoter methylation by acting as a sponge for miR-106b-5p to regulate sorafenib treatment sensitivity of hepatocellular carcinoma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies revealed the important functions of ceRNA network in tumor proliferation, antiapoptosis, metastasis and other tumor development processes. For example, circ3823 contributes to growth, metastasis and angiogenesis of colorectal cancer by absorbing miR-30c-5p and mediating TCF7 [ 48 ]. In addition to this, the resistant tumors showed significant expression changes of circRNAs, CircMEMO1 modulates the promoter methylation by acting as a sponge for miR-106b-5p to regulate sorafenib treatment sensitivity of hepatocellular carcinoma [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30c-5p was reported to be an important OS regulator by multiple studies [ 86 88 ]. In colorectal cancer, circ3823 functioned as a ceRNA of miR-30c-5p, alleviating the repressive effect of miR-30c-5p on TCF7 which upregulated MYC and CCND1 and eventually led to cancer initiation and metastasis [ 89 ]. Hu et al identified an oncogenic circASAP1 through circRNA sequencing in patients with HCC, which was proved to be associated with cancer initiation and metastasis via miR-326/miR-532-5p-MAPK1/CSF-1 signaling, respectively [ 90 ].…”
Section: The Mechanisms Of Ros-ncrnas Axis In Cancer Progressionmentioning
confidence: 99%
“…However, the possible role of miR-30c-5p as a biomarker for early diagnosis or development of recurrence needs further investigation. miR-30c-5p studied here has been shown to be involved in other cancers such as colorectal cancer [32,33], non-small cell lung cancer [34,35], gastric cancer [36], pancreatic ductal adenocarcinoma [37], renal cell carcinoma [38,39], hepatocellular carcinoma [40][41][42][43], breast cancer [44][45][46][47][48], laryngeal cancer [49], and other malignancies. For example, in gastric cancer, miR-30c-5p suppresses migration, invasion, and epithelial to mesenchymal transition via targeting MTA1 [36].…”
Section: Discussionmentioning
confidence: 85%